PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP MINAT BELI SMARTPHONE MEREK SAMSUNG - Made Dena Suputra; Ni Luh Wayan Sayang Telagawathi (Taksasila Edukasi Insani, 2026)
This study aimed to examine the influence of brand image and product quality on consumers’ purchase intention toward Samsung smartphones in Singaraja City. The research was motivated by the declining Top Brand Index of Samsung over the last five years, indicating a potential decrease in consumer purchase intention. This study used a quantitative approach with a causal research design. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling. The data were analyzed using multiple linear regression analysis. The results showed that brand image had a positive and significant effect on purchase intention. Product quality also had a positive and significant effect on purchase intention. Simultaneously, brand image and product quality significantly influenced consumers’ purchase intention toward Samsung smartphones in Singaraja City. Keywords : Brand Image, Product Quality, Purchase Intention